Operational rules for implementing sincere software agents in corrective and preventive actions environment - Jaafar N.H.; Ahmad M.S.; Ahmad A. (Springer Verlag, 2023)
Artificial intelligence; Human resource management; Information systems; Quality management; Agent-based systems; Management environments; Organizational management; Preventive action; Sacrifice; Sincerity; Software agent technology; Successful management; Software agents